Distribution and population structure of North Atlantic harbour seals (Phoca vitulina) - Liselotte Andersen (NAMMCO Scientific Publications, 2010)
A review of the known geographical distribution and current knowledge on the genetic population structure of harbour seals (Phoca vitulina) in the North Atlantic is presented. Based on a synthesis of the results fromfive different studies of neutral geneticmarkers (mtDNAand nuclear microsatellites, mainly) twelve genetically distinct populations were identified in the North Atlantic: USA/Canada, Iceland, west coast of Norway, Ireland-Scotland, English east coast, Channel area, Wadden Sea, Limfjord, Skagerrak, Kattegat, West Baltic, and East Baltic. Most of the studies addressed the population structure at the regional level, while only a few addressed the structuring at a local level, i.e. within countries. Due to the limited number of studies conducted, the identified population units were considered preliminary andmore detailed, local studieswould probably reveal structuring on a finer scale. The choice of genetic markers, their properties, resolution in time and applicability in population structure studies is shortly discussed and compared to ecological methods used to delineate populations.